Efficacy of preprocedural mouth rinses (Chlorhexidine, essential oil, and hydrogen peroxide) in reducing bacterial aerosols during dental scaling - Soma Hoseyni; Masoumeh Rostamzadeh; Himen Salimizand; Arian Azadnia; Farshad Rahimi; Shabnam Khalifehzadeh (BMC Oral Health)
Abstract Aim This study aimed to compare the efficacy of mouth rinsing with chlorhexidine, essential oil, and hydrogen peroxide mouthwashes in reducing bacterial infection in aerosols produced during dental scaling. Materials and methods Eighty subjects were randomly assigned to four groups. Ten minutes before treatment, participants rinsed for 1 min with 10 mL of either chlorhexidine, essential oil, hydrogen peroxide, or water. Blood agar plates were used to collect aerosols during the scaling procedure, with plates placed at the patient’s chest, dentist’s chest, and assistant’s chest. Plates were exposed for 30 min during and after treatment, incubated at 37 °C for 48 h, and the total number of colony-forming units (CFUs) was counted and analyzed using SPSS-24 software. Results The mean age of participants was 35.01 years, with 57.5% female and 42.5% male. A statistically significant difference was observed in the number of bacterial colonies on the patient’s chest plates (882.56 CFUs), dentist’s chest (99.84 CFUs), and assistant’s chest (48.49 CFUs) (p value < 0.001). Chlorhexidine mouthwash significantly reduced bacterial growth compared to the other groups. Conclusion Rinsing with chlorhexidine mouthwash before dental treatment effectively reduces bacterial contamination in aerosols, thereby lowering the risk of infection for dental personnel and patients. Clinical trial number Not applicable